Degree of Hearing Loss and Students' Quality of Life at a State-Owned Extraordinary School in Jember Indonesia - Bachtiar Hidayat, Aldy; Rumastika, Nindya Shinta; Rachmania, Sheilla (Journal of Community Medicine and Public Health Research, 2024)
Hearing loss is one of the health problems that can be caused by genetic factors, anatomical abnormalities, trauma to the ears and head, ototoxic drugs, and bacterial meningitis. People with hearing loss may have physical, intellectual, and mental limitations that can hinder daily activities and affect quality of life. Extraordinary School (Sekolah Luar Biasa/SLB) is the school that serves school-age children with special needs or those having a physical or/ mental disorder. This study aimed to determine the relationship between the degree of hearing loss and the quality of life of students with hearing disabilities at SLB Negeri Jember, Indonesia. This study used an analytic observational research design. The total number of samples in this study was 23 students who met the inclusion and exclusion criteria, then an audiometer examination and a questionnaire survey were carried out. This study used the Pediatric Quality of Life Inventory (PEDS-QLTM) questionnaire. The statistical test used was the Spearman correlation test. Interpretation of the results was considered to have a significant correlation if the p-value <0.05. The result of statistical analysis using Spearman's rank shows the relationship between the degree of hearing loss and the physical function of students with hearing loss at the SLB Negeri Jember shows a significance value of 0.184. The relationship between the degree of hearing loss and emotional function obtained a result of 0.005. The relationship between the degree of hearing loss and social functioning shows a significance value of 0.561. The relationship between the degree of hearing loss and school functioning showed a significance value of 0.016. The results were considered to have a significant correlation if the p-value <0.05. In conclusion, hearing loss was found not to have significant relationship with physical and social functioning in students with hearing disabilities at SLB Negeri Jember, Indonesia